Iron ore review 1990-1998 - Sousa,Wilson Trigueiro de (2002)
One of the world's largest iron-ore reserves lies in Brazil. The country is a major iron-ore producer and exporter due to modern mines, an efficient railway and port network and skilled mining personnel. A review of this reality is presented in this paper. This review considers the general aspects of iron ore, such as definitions, geology, world resources and reserves, ore size specifications, mining, ore treatment and transport. Moreover, it summarizes the worldwide iron ore market in the 1990's.